Adaptive cooperative control for high-order nonlinear multiagent time-delay systems using barrier functions. Issue 2 (2020) - Song, Jiacheng; Ju, Yongfeng; Yan, Maode; Yang, Panpan; Zuo, Lei
Abstract: A novel adaptive backstepping controller is developed to achieve the asymptotic synchronization. The designed controller only contains the values of system states, and doesn't contain any other prior knowledge of system. Firstly, the designed controller regards the unknown system nonlinearities and the disturbance of state time-delay as "disturbance-like" terms, which are guaranteed to be bounded by using the pre-set barrier functions, such that any prior knowledge of system nonlinearities and state time-delay are released. Then, the "disturbance-like" terms are compensated adaptively by designing the novel compensator at each step, such that the synchronization errors are eliminated to zero eventually for each agent. It is proved that our developed controller guarantees the convergence on the basis of Lyapunov stability theory. Some simulations are shown to demonstrate the effectiveness and advantages of the developed method.